Pemberdayaan Kelompok Nelayan Desa Arakan Kabupaten Minahasa Selatan Dalam Diversifikasi Produk Olahan Ikan - Helen Jenny Lohoo; Joyce Christiana Valencia Palenewen (JURNAL PESISIR DAN LAUT TROPIS, 2021)
The purpose of this program is to empower the Women Fishermen group in Arakan Village, South Minahasa Regency, North Sulawesi Province in processing / diversifying fish products into shredded. This diversification of shredded fish is expected to increase production, management to be skilled and economically independent which in turn can increase people's income. The specific target of this activity is to produce shredded fish products that are superior in terms of taste, sanitation and hygiene, durability, and create jobs / businesses and strong management. The implementation methods applied to this program are 1) the production of shredded fish; 2) Approach methods to overcome partner problems, namely counseling, training, mentoring and evaluation; 3) Work procedures to support aspects of the problem, respectively, namely survey, counseling, training, evaluation, output, reporting.The result of this activity is an increase in the skills and knowledge or empowerment of the Women Fishermen group in Arakan Village, South Minahasa Regency, North Sulawesi Province in processing/diversifying fishery products, namely fish floss which is delicious and favored by panelists, packaged practically. This activity is expected; women in coastal areas can be empowered through economic activities based on fishery business so that they become a new locomotive in bringing the economy of fishing communities to be better.Â Keywords: empowerment, diversifying processed, fish products, Arakan village